2016
DOI: 10.2147/rru.s107852
|View full text |Cite
|
Sign up to set email alerts
|

Integrating diet and exercise into care of prostate cancer patients on androgen deprivation therapy

Abstract: Improved diagnosis and treatment regimens have resulted in greater longevity for men with prostate cancer. This has led to an increase in both androgen deprivation therapy (ADT) use and duration of exposure, and therefore to its associated adverse effects, such as sexual dysfunction, osteoporosis, reduced muscle mass, increased fat mass, and increased incidence of cardiovascular disease and type 2 diabetes. Given that the adverse effects of ADT are systemic, often debilitating, and difficult to treat, efforts … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
18
0
3

Year Published

2017
2017
2021
2021

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 21 publications
(21 citation statements)
references
References 97 publications
(146 reference statements)
0
18
0
3
Order By: Relevance
“…Additionally, while we did not find specific associations between BMI and trajectories of physical function over time, the use of more precise measures of body composition may have provided better information. Finally, we did not evaluate diet or nutrition, a critical factor contributing to changes in body composition in men who begin hormone therapy [35].…”
Section: Discussionmentioning
confidence: 99%
“…Additionally, while we did not find specific associations between BMI and trajectories of physical function over time, the use of more precise measures of body composition may have provided better information. Finally, we did not evaluate diet or nutrition, a critical factor contributing to changes in body composition in men who begin hormone therapy [35].…”
Section: Discussionmentioning
confidence: 99%
“…One of the side effects of ADT is the increase in fat mass and the development of metabolic syndrome . At onset of ADT, the majority of patients already have a diagnosis of overweight, therefore, proper diet counselling is indicated , but was rarely given as standard practice before pathway implementation. In addition to the positive effects of a diet intervention on cardiometabolic health, it can also support bone health .…”
Section: Discussionmentioning
confidence: 99%
“…Studies demonstrated that only the minority of PCa patients performs sufficient physical activity according to exercise cancer guidelines (Forbes, Blanchard, Mummery, & Courneya, ; Galvão et al., ). Therefore, strategies to enhance physical activity are indicated (Moyad, Newton, Tunn, & Gruca, ; Nguyen et al., ; Taaffe et al., ). PCa patients show a positive attitude towards exercise programmes (Cormie et al., , Green, Steinnagel, Morris, & Laakso, ).…”
Section: Discussionmentioning
confidence: 99%